Find expert advice and community support for all your questions on IDNLearn.com. Discover reliable and timely information on any topic from our network of experienced professionals.

Solve the system of equations:
[tex]\[
\begin{cases}
2x + y = -4 \\
3x + 5y = 29
\end{cases}
\][/tex]


Sagot :

To solve the system of equations:

[tex]\[ \left\{ \begin{array}{l} 2x + y = -4 \\ 3x + 5y = 29 \end{array} \right. \][/tex]

we need to find values for [tex]\(x\)[/tex] and [tex]\(y\)[/tex] that satisfy both equations simultaneously. Here are the steps:

1. Express [tex]\(y\)[/tex] from the first equation:

[tex]\[ 2x + y = -4 \implies y = -4 - 2x \][/tex]

2. Substitute [tex]\(y\)[/tex] into the second equation:

Substitute [tex]\( y = -4 - 2x \)[/tex] into [tex]\( 3x + 5y = 29 \)[/tex]:

[tex]\[ 3x + 5(-4 - 2x) = 29 \][/tex]

3. Simplify the equation:

[tex]\[ 3x - 20 - 10x = 29 \][/tex]

Combine like terms:

[tex]\[ -7x - 20 = 29 \][/tex]

4. Solve for [tex]\(x\)[/tex]:

Add 20 to both sides:

[tex]\[ -7x = 49 \][/tex]

Divide both sides by -7:

[tex]\[ x = -7 \][/tex]

5. Find [tex]\(y\)[/tex] using the value of [tex]\(x\)[/tex]:

Substitute [tex]\(x = -7\)[/tex] back into the expression for [tex]\(y\)[/tex]:

[tex]\[ y = -4 - 2(-7) \][/tex]

Simplify:

[tex]\[ y = -4 + 14 = 10 \][/tex]

So, the solution to the system of equations is:

[tex]\[ x = -7, \quad y = 10 \][/tex]

Therefore, the values are [tex]\(\boxed{x = -7}\)[/tex] and [tex]\(\boxed{y = 10}\)[/tex].